Implikatur Youtube Gita Wirjawan dan Relevansinya Bagi Pembelajaran Teks Cerpen di SMA - Andi Kurniawan; Atiqa Sabardila (Jurnal Pendidikan (Teori dan Praktik), 2026)
This type of research uses a qualitative approach. This study aims to describe the types of implicatures and theoretical pedagogical implications in learning short story texts contained in Gita Wirjawan's YouTube channel. The data obtained in this study are 1) 24 utterances containing implicatures in conversations on Gita Wirjawan's YouTube channel, 2) pedagogical implications in implicatures on Gita Wirjawan's YouTube channel towards learning short story texts. The episode of the data obtained amounts to one episode with a duration of 1 hour 56 minutes 4 seconds, the selection of the video is based on the reference of this study which refers to learning, not only in terms of content but also in terms of storytelling that can be used as material for students to write so that it is relevant to this study. The data collection technique uses documentation in the form of transcripts recorded in conversations on Gita Wirjawan's YouTube that contain implicatures. The data analysis technique uses listening and note-taking techniques. The data validity technique uses data triangulation. The results of this study are in the form of (1) types of implicatures obtained in Gita Wirjawan's YouTube channel which consist of 3 conventional implicatures, 8 specific conversational implicatures, 5 general conversational implicatures, and 8 scale implicatures (2) the results of this study theoretically from a teaching perspective, conversational implicatures in Gita Wirjawan's podcast can help in the process of learning short story texts, because they can function as storytelling tools to create implied meanings, characters, and morals in dialogue.